Modelling and Analysis of Regulatory Interventions for Sustainable Public Wi-Fi Programs: The Case of India - Agrawal, Sandeep; Sridhar, Varadharajan (Journal of Telecommunications and the Digital Economy, 2025)
Public Wi-Fi is a suitable technology alternative to mobile broadband for affordable Internet access. With a 2.6 billion population yet to be connected globally, many countries are formulating policies around Public Wi-Fi to bridge the digital divide. India lags considerably in broadband connectivity, with only 44% rural Internet/broadband density. Public Wi-Fi penetration in India is meagre compared to global deployments. The Indian government launched the Wi-Fi Access Network Interface (WANI) as an approved Public Wi-Fi infrastructure in December 2020 with the dual objectives of encouraging local entrepreneurs to become Public Data Offices (PDOs) and offering citizens affordable high-speed Wi-Fi Internet service. However, the scheme has so far met with limited success. The sustainability of these PDOs is critical for the success of the program. We develop an Agent-Based Model of the WANI ecosystem by incorporating the Bass diffusion model for users’ adoption of Internet data service offered by PDOs. Our simulations indicate that offering a one-time subsidy, capping the market share of PDOs, and fixing a lower Internet backhaul tariff will lead to more sustainable and competitive Wi-Fi markets.